Structural damage identification with admittance signatures of smart PZT transducers - Akshay Surendra Kumar Naidu (2008)
The concepts of vibration-based methods are integrated with the e/m impedance method to extend its applicability for damage location identification and damage growth characterization. Also, Bayesian network model is integrated to e/m impedance-based structural health monitoring.